CHALCOPHILE METALS IN THE FORMATION PROCESSES OF MAGMA AND THE EARTH CORE - Ryabchikov I.D.; Orlova G.P.; Babanskiy A.D.; Magazina L.O.; Tsepin A.I. (My University, 1999)
The aim of this study was to estimate the contents of sulfur in the silicate Earth, using a quantitative model for the generation of NMORB basalts in the course of the polybaric dynamic melting of a pyrolite source. Also used were the data available for the contents of chalcophile metals in the mantle peridotite and basalt, compared to the analysis of the behavior of these components during the partial melting of sulfide-bearing peridotite. The content of sulfur in the Earth mantle was estimated to be 300 g ton -1. Using the experimental data available for silver solution in basalt magma over a wide range of oxygen fugacity values, it was found that the coefficient of silver distribution in the basalt melt over the wide range of oxygen volatility between the sulphide and silicate phases was close to 100. This confirmed the conclusion of the high silver extraction capability of a sulfide melt. The relatively poor silver contents in the silicate material of the Earth (that is, in the primitive mantle) can be explained in terms of the three-stage model of heterogeneous accretion.
Keywords: CHALCOPHILE METALS; FORMATION PROCESSES OF MAGMA; NMORB BASALTS QUANTITATIVE MODEL